Immune checkpoint inhibitors and cancer-related cognitive decline: a propensity score matched analysis in active chemotherapy patients - Jian, Guangmin; Zeng, Jiling; Lu, Jun; Wang, Weidong; Jiang, Yongluo; Huang, Tong; Niu, Yu Si; Chai, Zhoufang; Qi, Xin; Liu, Nianqi; Wang, Youlong; Liu, Cantong; et al. (Frontiers in Immunology, 2025)
BackgroundWe investigated whether 1-year trajectories of cancer-related cognitive decline (CRCD) would be different in patients with chemotherapy combined with immune checkpoint inhibitors (chemoICI group) as compared with chemotherapy alone (chemo group).MethodsParticipants scheduled with or without ICI were prospectively recruited from three academic hospitals and followed up for 1 year in four sessions. Subjective and objective CRCD were measured by Perceived Cognitive Impairment (PCI) and Montreal Cognitive Assessment (MoCA), respectively. Primary endpoints were MoCA and PCI score changes and minimal clinically important difference (MCID), which was defined as threshold for meaningful impairment events. Propensity score matching (PSM) was performed for group comparison using logistic regression with covariates including age, cancer stage, and baseline cognitive scores. Linear mixed models adjusted for repeated measures.ResultsOut of 1557 recruited patients PSM yielded 460 patient pairs (1:1). Mean PCI and MoCA scores of both groups reached MCID at 12-month session in both groups. In chemoICI, MoCA score changes were significantly lower in the 12-month session, and PCI score changes were lower in the 6, 9, and 12-month sessions than chemo (P<0.05). One-year meaningful impairment events risks were 0.44 and 0.56 in chemoICI, significantly higher than that of chemo (0.35 and 0.38, P<0.01). Significant differences were found in mean event-free survival time in patients with and without irAE in chemoICI subgroup analysis.ConclusionsOur findings suggest that combining chemotherapy with ICIs may exacerbate CRCD compared to chemotherapy alone. However, reliance on screening tools and self-reported measures limits definitive conclusions. Future studies incorporating comprehensive neuropsychological assessments are warranted. This study underscores the importance of using comprehensive cognitive assessments in future research to better understand the impact of ICIs on cognitive function.